Two Typical Patterns of Regional PM2.5 Transport for Heavy Air Pollution Over Central China: Rapid Transit Transport and Stationary Accumulation Transport - Wang, Ying; Bai, Yongqing; Zhi, Xiefei; Wu, Kai; Zhao, Tianliang; Zhou, Yue; Xiong, Jie; Zhu, Shoupeng; Zhou, Wen; Hu, Weiyang; Zhang, Ling; Meng, Kai (Frontiers in Environmental Science, 2022)
The regional transport of air pollutants has been identified as an essential factor that affects air quality over downwind receptor areas. The Twain-Hu Basin (THB) over central China is a key receptor region in regional PM2.5 transport because of its unique geographical location. In this study, we first identified typical severe PM2.5 episodes induced by regional transport to the THB corridors during 2015–2020 in winter, characterized by rapid transit transport (RTT) and stationary accumulation transport (SAT). Next, we revealed the meteorological mechanisms of the formation of two regional PM2.5 transport patterns. The similar meteorological conditions trigger the RTT and SAT with high-concentration PM2.5 air mass from the upstream regions transporting to the THB under the strong northerly winds in the southward advance of cold air mass, and the average rising rate of PM2.5 concentration in RTT (12.5 μg/m3/h) is faster than that in the SAT (5.7 μg/m3/h). However, the meteorological conditions evolve differently in the two types of RTT and SAT. For RTT with fast passage of cold air, the THB is located behind the strong cold front in the later stage, and these events were rapid ended by northerly winds and wet scavenging of precipitation. For SAT with slow accumulation of cold air, the THB is mainly occupied by a weak high-pressure system with weak wind speed, strong descending airflow, and low atmospheric boundary layer height, trapping air pollutants accumulated in the THB, resulting in persistent heavy pollution incidents. This study provides new insights into the meteorological mechanism on formation of severe air pollution episodes over a receptor region in regional transport of air pollutants.